Green Intentions: Field Research and Data-Driven Analysis of Customers’ Purchasing Patterns - Camilla Carpinelli; Einar Torfi Einarsson Reynis; Anna Sigríður Islind; Hlynur Stefánsson; María Óskarsdóttir (Sustainability, 2022)
Sustainability and sustainable consumption have become key factors in the battle with global warming in general and environmental pollution in particular. To motivate consumers to make sustainable purchasing decisions, it is necessary to understand consumers’ attitudes and purchasing behavior towards green products. This study analyzed if the environmental impact of select products had measurable effects on consumers’ purchasing behavior by analyzing purchasing data from a large retail store in Iceland spanning two years. To gain insight into consumers attitude and intentions towards green products, a survey was conducted which received 166 responses, and will be used in comparison with the purchasing data analysis and testing. The main goal of this study is to analyze the gap between consumers’ intent to consumers’ actual green purchasing. The results of this study will demonstrate that there is an actual difference in this field.